2013
DOI: 10.1111/j.1469-0691.2011.03742.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genetic diversity of Staphylococcus aureus small-colony variants in cystic fibrosis patients

Abstract: Staphylococcus aureus small-colony variants (SCVs) are being isolated more frequently in cystic fibrosis (CF) patients. We aimed to determine the prevalence of S. aureus SCVs and their phenotypic and genotypic properties in CF patients admitted to a university hospital. Specimens of 248 patients were examined during a period of 11 months. Colonies supposed to be SCVs were evaluated on Columbia blood agar, mannitol salt agar, and brain-heart infusion agar with 5% NaCl (BHIA 5% NaCl). Strains were confirmed by S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
2
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 26 publications
3
50
2
3
Order By: Relevance
“…During the last 40 years, nine prospective studies dealing with the culture of S. aureus SCVs from the airways of almost 2,000 cystic fibrosis (CF) patients (the numbers of patients in the different studies ranged from 14 to 594) during a period of 3 to 34 months (mean, 13 months) have been published from 6 countries, including the United Kingdom, United States, Germany, Belgium, Switzerland, and Turkey (30,31,(57)(58)(59)(60)(61)(62)(63) (Table 3). This special interest in SCV occurrence and prevalence in CF is due to some special characteristics of CF airways, which are explained briefly in the following paragraph.…”
Section: Cystic Fibrosis Airway Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the last 40 years, nine prospective studies dealing with the culture of S. aureus SCVs from the airways of almost 2,000 cystic fibrosis (CF) patients (the numbers of patients in the different studies ranged from 14 to 594) during a period of 3 to 34 months (mean, 13 months) have been published from 6 countries, including the United Kingdom, United States, Germany, Belgium, Switzerland, and Turkey (30,31,(57)(58)(59)(60)(61)(62)(63) (Table 3). This special interest in SCV occurrence and prevalence in CF is due to some special characteristics of CF airways, which are explained briefly in the following paragraph.…”
Section: Cystic Fibrosis Airway Infectionmentioning
confidence: 99%
“…Furthermore, we showed that SCVs were better able to persist intracellularly in eukaryotic cells than their isogenic normal S. aureus strain, supporting the hypothesis that S. aureus and especially SCVs can hide intracellularly, where they are protected against the host defense and antibiotic therapy. Yagci et al reported a prevalence of 8.1% (n ϭ 20) in their 248 CF patients during an 11-month study (63). Six of 48 SCVs (12.5%) were thymidine dependent and SXT resistant, and there was a history of SXT treatment in five patients.…”
Section: Cystic Fibrosis Airway Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal fenotip Staphylococcus aureus izolatlarına göre yavaş üreyen, pigmentsiz, hemoliz yapmayan, çok küçük kolonilerle karakterize S. aureus küçük koloni varyantlarının (KKV), atipik fenotipik ve metabolik özellikleri nedeniyle laboratuvar tanısı güçlükle konabilmektedir 1 . Klinik mikrobiyoloji laboratuvarlarında doğru tanımlanması gereken bu suşlar, atipik koloni morfolojileri nedeniyle gözden kaçırılabilmekte veya sıklıkla kontaminasyon olarak değerlendirilerek hatalı sonuçlar verilebilmektedir 2 .…”
Section: Sayın Editörunclassified
“…Polyclonality can also occur when the patient is infected with different clones from the same section of skin, which may occur either during surgery or afterwards and is likely a more common phenomenon (7). Several reports have found polyclonality in monomicrobial infections among isolates of small-colony variant staphylococci, which present phenotypically different colonies (8)(9)(10), but this phenomenon may also happen among phenotypically identical colonies.…”
mentioning
confidence: 99%